Plant-derived extracellular vesicles: an alternative and complementary therapeutic approach for genitourinary tumors - Huang, Yuqing; Zhang, Yunmeng; Lou, Kecheng; Feng, Shangzhi; Feng, Guoqiang (Frontiers in Cell and Developmental Biology, 2025)
Over the past four decades, the incidence of genitourinary tumors has risen significantly, becoming a major global health concern. This trend necessitates the exploration of more effective treatment strategies. Although considerable progress has been made in treatments such as endocrine, immune, and targeted therapies, these malignancies often remain uncontrolled, especially when metastatic. Recent advances in nanobiomedicine have revealed plant-derived extracellular vesicles as a novel and promising anti-cancer therapeutic option. These natural nanoparticles exhibit high biocompatibility, targeted delivery capability, and renewable properties, positioning them at the forefront of innovative cancer treatment strategies. Their inherent anti-cancer properties—such as inducing cell cycle arrest, promoting apoptosis, and inhibiting metastasis—may offer new alternatives for treating genitourinary cancers. This review summarizes current research on plant-based treatments for genitourinary tumors, focusing on the potential mechanisms and applications of plant-derived extracellular vesicles, thereby suggesting new nanoscale alternative and complementary therapeutic avenues.